(untitled) (Journal of the College of Basic Education, 2026)
The English language has its own distinctive grammatical rules, which form the foundation of the language in real use. Thus, teaching grammar is so important for EFL teachers. Mainly, there are two approaches for teaching grammar; deductive and inductive. Teachers adopt either the deductive approach which is rule- given, or the inductive approach which refers to rule -driven. The study aims to explore the EFL college instructors’ preference and use of deductive and inductive approaches for teaching grammar. Two questionnaires were adopted and answered by the sample. The sample consists of 24 instructors who teach college students. The results revealed that the majority EFL college instructors were concentrating on using a deductive rather than an inductive approach to teaching grammar and they believe in the effectiveness of the deductive approach in teaching grammar. In conclusion, TEFL is in rapid development and many new trends and methods appear, so college instructors should be aware of them and they should also vary the method of teaching used in the lecture to break boredom , to stimulate critical thinking, and to raise enthusiasm .